Penanaman Rumput Akar Wangi (Chrysopogon zizanioides) Sebagai Upaya Mitigasi Bencana Longsor Di Desa Giri Madia Kecamatan Lingsar Kabupaten Lombok Barat - Farista, Baiq; Arben Virgota; Astrini Widiyanti; Aida Muspiah; Nur Indah Julisaniah; Komala Mala Hayati; Riyana Sulastika; Husnul Almubarok (Universitas Mataram, 2024)
Giri Madia Village, Lingsar District, West Lombok Regency is one of the villages prone to landslides. The results of the study showed that around 49.87 Ha of land is classified as a high landslide-prone area. Therefore, mitigation efforts were made to reduce the risk of landslides by utilizing vetiver grass (Chrysopogon zizanioides). This community service activity was carried out through collaboration between the community service team, the village government, and the Giri Madia Village community, from December 2023 to February 2024. The program implementation started from preparation (observation, finding partners, and licensing), implementation (provision of seeds and planting), and monitoring. Coordination with the village government and the local community was carried out through open discussions. The seedling planting activity was carried out by the community service team and the community in three predetermined locations. The monitoring results showed that almost all of the vetiver grass that was planted was able to survive even though it was not watered regularly by the community. Community activities, namely cutting down trees around the vetiver grass planting location, caused more than a third of the total seedlings to die from being hit. In addition, the obstacles that arise are the lack of community participation in grass care such as watering and fertilizing. This can be caused by the lack of public awareness to help care for the fragrant root grass seeds. The community feels that they do not have time to monitor because of their daily activities of earning a living.